Prevalence and Risk Factors Associated with Sub-Clinical Mastitis in Kundhi Buffaloes - Hassina Baloch; Rahmatullah Rind; Aslam Parvez Umerani; Abdul Latif Bhutto; Shahid Hussain Abro; Muhammad Rafique Rind; Rani Abro; Huma Rizwana; Asghar Ali Kamboh; Ahmed Khan Baloch (Journal of Basic & Applied Sciences, 2016)
The present study aimed to elucidate the magnitude and distribution of subclinical mastitis and associated risk factors in ‘Kundhi’ buffaloes of Hyderabad, Tandojam and Tando Allahyar locations of the province of Sindh, Pakistan. Milk samples (n=840) collected from 210 buffaloes were evaluated for the presence of subclinical mastitis in buffaloes using California Mastitis Test (CMT) and severity; moderate, severe, more severe, most severe. The positive samples were further processed for isolation and identification of bacterial pathogens. The overall intensity of subclinical mastitis at animal level was recorded as 54.29% while significantly higher prevalence (P<0.05) of subclinical mastitis was observed in buffaloes of Tandojam (60.56±0.996%) location. The prevalence of the subclinical at quarter-wise noted as 39.29% given maximum frequency (11.31±0.085%) with hind left quarters. The age and parity were found potential risk factors in Kundhi buffaloes, and susceptibility to subclinical mastitis was higher beyond the age of 6-9 years and 4-7 calving. The higher prevalence as well as the intensity of the disease was determined in buffaloes located at Tandojam than Hyderabad and Tando Allahyar. The ailment was higher in animals at 4th lactation likewise crossing 6 years of age and 4-7 parity. The old age animals were more prone to subclinical mastitis than the younger animals. Overall, the prevalence of the subclinical mastitis at animal and quarter levels was observed in buffaloes.